Implementation and realization of a kossel diffraction pattern simulation application - SEMASSOU, GUY CLARENCE (My University, 2021)
To better understand some of the local metallurgical mechanisms, it is necessary to have information about the scale of the stress gradient in the vicinity of a grain boundary or around a precipitate. This measurement is accessible by Kossel microdiffraction. Diffraction consists of the emission of Kossel cones, which are then intercepted by a screen. This leads to an image that can be used to trace the deformation field. The simulation technique is best suited to this purpose. The present work falls within this framework and aims on the one hand to geometrically model the phenomenon and on the other hand to develop an application in Java language for digital simulations of the Kossel cliché. The methodology adopted is to take into account all the parameters on which the phenomenon depends to establish the geometric model which has been programmed in the JAVA language with a view to making a simulation application comprising 14 interacting classes. The result obtained after an example of simulation is rather satisfactory and promising. However, a comparison will have to be made for the complete validation of the model. This will be the subject of another publication later.
Keywords: Kossel Micro Diffraction; Cone; Observation Screen; Deformation Field; Image